On intuitionistic fuzzy hyperideals in Γ-semihypergroups through left operator semihypergroup - Hila, Kostaq; Abdullah, Saleem; Dine, Jani (Utilitas Mathematica, 2016)
In this paper, the operator semihypergroups of a Γ-semihypergroup have been brought into use to study r-semihypergroups in terms of intuitionistic fuzzy subsets. This is accomplished by obtaining some fundamental relationships of a Γ-semihypergroup and its operator semihypergroup in terms of intuitionistic fuzzy subsets, intuitionistic fuzzy hyperideals and intuitionistic fuzzy hyperideal extension. Using these in obtaining some characterization theorems of Γ-semihypergroups in terms of intuitionistic fuzzy subsets, we highlight the effectiveness of operator semihypergroups in the study of Γ-semihypergroups in terms of intuitionistic fuzzy subsets.